Measurement of liver and spleen stiffness by shear wave elastography as a noninvasive evaluation of esophageal varices in hepatitis C virus-related cirrhosis - Alaa E Mahmoud Hashim; Mustafa M Shakweer; Farid F Attia; Hany M Awadallah; Fathya M Elraaey; Abdelhakam M Ibrahem (Wolters Kluwer Medknow Publications, 2017)
Background Several noninvasive methods have been developed to predict esophageal varices (EVs) in patients with cirrhosis aiming to restrict endoscopic screening. Recently, two-dimensional shear wave elastography (2D-SWE) was evaluated for this purpose. The aim of this study was to evaluate the use of 2D-SWE for liver stiffness measurement (LSM) and spleen stiffness measurement (SSM) for prediction of EV presence and grading. Patients and methods This study included 100 patients with hepatitis C virus cirrhosis who were subjected to upper endoscopy for detection and grading of EV as well as LS and SS measurements using 2D-SWE. Results There was a significant difference between patients with and without EV regarding LS and SS (P<0.001). The measurement LS at cutoff of 16.2 kPa and SS at cutoff of 42.7 kPa by 2D-SWE predicted the presence of EV with sensitivity of 89.8 and 94.9%, respectively, and specificity of 57.6 and 87.9%, respectively. Moreover, at cutoffs of 19.6 and 51.5 kPa for LS and SS, respectively, the presence of high-risk EV was predicted with sensitivity of 77.5 and 85%, respectively, and specificity of 63.4 and 84.6%, respectively. Conclusion The measurement of LS and SS by 2D-SWE predicted the presence of EV and high-risk EV in patients with cirrhosis, with more sensitivity and specificity for SS than LS.